Spatial Framework for the Assessment of Road Traffic Accidents in Karachi - Salman Zubair; Syed Jamil Hasan Kazmi (Journal of Basic & Applied Sciences, 2013)
Karachi, the most populous city of Pakistan, is entangled by an ever increasing health problem of Road Traffic Accidents (RTAs) in the recent past with ranked 4th in the world stats of highest road fatalities cities. The most devastating problem is that it is affecting the most productive age group. Nearly 300 RTA victims were interviewed last year and questioned about different socio-economic aspects of road crashes. This has demonstrated that the RTAs cases were observed between the age group of 18-45 years in Karachi. The problem is not only resulting financial losses but also social burden as well as pain, grief, psychological trauma in many cases and suffering for the effects which is certainly an irreparable damage. The prime objective of this study is to highlight the spatial variation most affected age group under threat of road traffic accidents in Karachi. This has been achieved by using a stratified random sampling technique and targeting the effects of RTA. Information was collected and analyzed and spatial pattern of RTAs in terms of accident location has been displayed with high and low RTA cases caused injuries and fatalities. Town based Road Accidents maps were developed in ArcGIS 10.1 to show the spatial patterns of road accidents. This study approaches with emphasis the miserable outcome of road accidents on the specific age grouped people because they are mostly involved in road crashes and also the future prospect of the country.